History of Friedrich II of Prussia $1 (BVolume 19s - Carlyle, Thomas, 1795-1881 (Salt Lake City, UT : Project Gutenberg, 2008)
"History of Friedrich II of Prussia $1 (BVolume 19" by Thomas Carlyle is part of a six-volume biography published between 1858 and 1865. This monumental work chronicles the life of Frederick the Great, King of Prussia, born from Carlyle's decades-long fascination with his subject. The Scottish historian devoted thirteen laborious years to the project, traveling twice to Germany, studying battlefields, and working through immense source materials. Contemporary critics praised it as supremely witty, morally penetrating, and filled with vivid characters that seem to bleed with life$1 (Ba testament to literary genius. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/History_of_Friedrich_II._of_Prussia,_Called_Frederick_the_Great
Release date is 2008-06-16
Produced by D.R. Thompson and David Widger
Keywords: Social problems; Frederick II, King of Prussia, 1712-1786; Prussia (Germany) -- History -- Frederick II, 1740-1786